Penguatan Posyandu dalam Pencegahan Stunting Melalui Deteksi Dini Berbasis Aplikasi dan Pendampingan Wirausaha di Sumatera Utara - Gunawan, Roni; Fitriani, Arifah Devi; Siregar, Dian Maya Sari; Asrul, Asrul; Siregar, Dahrul; Sugito, Sugito (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Reducing the stunting rate is still a national priority at this time, one of the important pillars that can be strengthened is monitoring and evaluation. One way is through early detection using the application as a monitoring medium. The implementation is the Posyandu which incidentally is the spearhead in the field, in order to strengthen the Posyandu efforts, the Posyandu needs to be supported to be economically productive and able to use the application. The method used is entrepreneurship training and application use, application use assistance, and entrepreneurial assistance. The results of this activity are able to use applications so that they are able to detect stunting toddlers early, then Posyandu has a productive business which part of the profits are used to help the operation of Posyandu